Early Childhood Tolerance in Minority Areas: A Foundation for Addressing Intolerance Problems in Indonesia - Nadlifah; Abdul Latif, Muhammad; Toyba Humaida, Rifka; Rismiyati Setyaningrum, Helda; Sarah, Siti (Universitas Pendidikan Ganesha, 2023)
Cases of intolerance, fanaticism, radicalism, and terrorism in Indonesia still occur frequently, causing commotion. Amid the commotion of this issue, it is essential to take preventive measures from an early age. This research aims to analyze tolerance implementation from an early age in minority areas in early childhood education institutions. This research method uses qualitative field research with a case study approach. Data collection techniques used passive participant observation, semi-structured interviews, and documentation. The analysis used was thematic analysis with validity testing in the form of triangulation of sources and techniques. This research shows that Gajahwong School implements tolerance by starting with initial, core, and closing activities. The values of tolerance developed are mutual respect, care, respect for friends' opinions, and cooperation between children. The impact of tolerance from an early age at Gajahwong School provides a foundation for children to tolerate each other, improving human, family, and environmental resources. The findings of this research contribute in the form of knowledge and an overview of the implementation of tolerance from an early age in dealing with radicalism in Indonesia.